2009
DOI: 10.1111/j.1440-1789.2008.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin matrix provides a suitable scaffold for bone marrow stromal cells transplanted into injured spinal cord: A novel material for CNS tissue engineering

Abstract: Recent basic experiments have strongly suggested that cell transplantation therapy may promote functional recovery in patients with spinal cord injury (SCI). However, a safe and efficient transplantation technique still remains undetermined. This study, therefore, was aimed to clarify whether fibrin matrix could be a useful scaffold in bone marrow stromal cell (BMSC) transplantation for the injured spinal cord. To clarify the issue, three-dimensional structure of fibrin matrix was assessed and the green fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 43 publications
0
75
0
Order By: Relevance
“…Alternative materials such as gelatin/-tricalcium phosphate (Yang et al, 2005), poly(L-lactic acid) (PLA) , poly(L-lactic-co-glycolic acid) (PLGA) (Jeon et al, 2007;Shen et al, 2009), hyaluronic acid (Kim and Valentini, 2002), fi brin gel (Itosaka et al, 2009) or porous hydroxyapatite composites (Sopyana et al, 2007) are under study. The recent developments in the research of BMP delivery carriers have been comprehensively revised by Bessa et al (2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative materials such as gelatin/-tricalcium phosphate (Yang et al, 2005), poly(L-lactic acid) (PLA) , poly(L-lactic-co-glycolic acid) (PLGA) (Jeon et al, 2007;Shen et al, 2009), hyaluronic acid (Kim and Valentini, 2002), fi brin gel (Itosaka et al, 2009) or porous hydroxyapatite composites (Sopyana et al, 2007) are under study. The recent developments in the research of BMP delivery carriers have been comprehensively revised by Bessa et al (2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a couple of studies showed that chitooligosaccharides (COSs), the biodegradation products of chitosan, promote peripheral nerve regeneration and functional recovery in the rat sciatic nerve crush injury model and rabbit common peroneal nerve crush injury model, suggesting their potential application in peripheral nerve repair as neuroprotective agents (Gong et al, 2009;Jiang et al, 2009). Moreover, immunophilin FK506 combined with biodegradable chitosan guide provides neurotrophic and neuroprotective actions, promoting nerve regeneration in a rat sciatic nerve defect model .…”
Section: Chitosan Conduits Combined With Neurotrophic Factors or Neurmentioning
confidence: 99%
“…A photocrosslinkable hydrogel based on chitosan has been in vitro successfully characterized and proposed as a new adhesive for peripheral nerve anastomosis (Rickett et al, 2011). Chitosan has further been used in combination with other biomaterials for bridging peripheral nerve gaps (Fan et al, 2008;Jiao et al, 2009;Lin et al, 2008;Simoes et al, 2010;Xie et al, 2005;Xie et al, 2008;Xu et al, 2009). Chitosan-polylactid acid (PLA) composite nerve conduits showed good biocompatibility and permeability, good mechanical strength, intensity, and elasticity, facilitating microsuture manipulation, and they provide enough mechanical strength to support nerve regeneration.…”
Section: Chitosan For Peripheral Nervous System Repairmentioning
confidence: 99%
See 2 more Smart Citations